From From teachers to monuments. Emblematic sculptures in Ibero-American academic institutions - García Lirio, Manuela (REVISTA ELECTRONICA IBEROAMERICANA, 2025)
The university, as a space of knowledge, has become a key identity for those cities that have these educational institutions. This article aims to address a heritage itinerary focused on the value of sculpture as a key heritage element in different university campuses, museums and university collections in Spain, Portugal, Argentina, Chile, Mexico and Venezuela. Sculpture has gone from having a pedagogical and cultural dimension to becoming an icon of the university academic community, with a public and commemorative character.